A review of research on medical image confidentiality related technology coherent taxonomy, motivations, open challenges and recommendations - Bahbibi Rahmatullah (Tanjung Malim, 2023)
A review of research on medical image confidentiality related technology coherent taxonomy, motivations, open challenges and recommendations by Bahbibi Rahmatullah